Sebaran Spasial Plankton dan Klorofil-a sebagai Indikator Penentuan Daerah Potensial Penangkapan Ikan di Perairan Gili Trawangan: Spatial Distribution of Plankton and Chlorophyll-a as Indicators for Determining Potential Fishing Grounds in the Waters of Gili Trawangan - Salwa, Hanna; Larasati, Chandrika Eka; Paryono (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2024)
A high abundance of plankton serves as an indicator of water fertility and can be used to identify potential fishing grounds. Fishing grounds are determined by analyzing the presence and density of fish schools in a given area. This study aims to assess the spatial distribution of phytoplankton, zooplankton, and chlorophyll-a to identify potential fishing zones. The research was conducted in March 2024 in Gili Trawangan, covering 12 sampling stations. Sampling locations were selected using a purposive sampling method based on water characteristics, prioritizing areas with high plankton and chlorophyll-a concentrations. The results indicate that the southern waters of Gili Trawangan, particularly Stations 03 and 05, have strong potential as fishing zones due to their high phytoplankton, zooplankton, and chlorophyll-a concentrations. Similarly, Station 09 in the eastern waters exhibits the highest abundance of all parameters; however, its proximity to the harbor makes it unsuitable for fishing activities. Overall, Gili Trawangan meets the criteria for a viable fishing ground due to the high abundance of plankton species, which serve as a primary food source for fish. The dominant plankton species in these waters include Coscinodiscus sp., Rhizosolenia sp., and Nauplius sp.. A higher plankton abundance correlates with increased water productivity, leading to greater fish availability in these waters.